Thermo-Economic Analysis of Simple Cycle Steam Power Plant - Abed, Mohammed Sh.; Sultan, Hussein S.; Abood, Falah A. (Basrah Journal for Engineering Sciences, 2023)
Thermal steam power plants represent the most important and dependable type for supplying the base load of electricity around the world. The thermos-economic analysis is an important tool for improving the performance of thermal steam power plants. In the present study, a thermo-economic analysis of a simple steam power plant for different boiler pressure was performed. The analysis comprises the energy, exergy, entropy, economics, and exergy-economic of a simple cycle steam power plant for different boiler pressure. The analysis was performed for a simple steam power plant with the constant output power of 10 MW and the boiler pressure is varied from 10 bar to 100 bar by a step of 10 bar. For each boiler pressure and constant output power, firstly, the fuel mass flow rate, steam flow rate, energy and exergy efficiency, and cost of electricity were calculated. Secondly, entropy generation, exergy destruction, and exergy efficiency for each component were calculated. Finally, exergy destruction economics for each component of the plant was performed. The results reveal that increasing the boiler pressure from (10 to 100 bar) for constant output power reduces the cost of electricity from (0.135 to 0.1025 $/kWh) due to a decrease in the fuel mass flow rate and an improvement in the thermal cycle and exergy efficiency. Also, when the boiler pressure increases, the exergy destruction for the pump increases, the exergy destruction for the boiler decreases, the exergy destruction for the turbine increases, and the exergy destruction for the condenser decrease.